White spruce dynamics in the forest-tundra ecotone, the southwest Yukon Territory. - Ayotte, Nicole. (University of Ottawa (Canada), 2002)
Dendrochronological techniques were used to study white spruce ( Picea glauca [Moech] Voss) dynamics in the altitudinal forest-tundra ecotone in the southwest Yukon Territory. At two sampling sites, all Picea glauca individuals within 9 delineated quadrats in the forest-tundra and forest were sampled to estimate dates of establishment and growth variations using tree-ring chronologies. Regeneration in the forest-tundra ecotone was low from the late 1800s to the mid-1900s, however has increased since the 1920s. Recent peak periods of establishment parallel increased radial growth trends, which may have resulted from the long-term warming trend of the 20 th century. Seedling proximity to pre-established individuals in the forest-tundra ecotone suggests regeneration from a local seed source. Growth in height of pre-established krummholz individuals accelerated around the 1950s. Tree establishment in the forest-tundra and forest appear to be influenced by summer temperatures of the current growing season, and a high degree of similarity in tree growth at different sites in the southwest Yukon suggests a regional response to a large-climate signal. An increase in krummholz height and improved seedling establishment in the forest-tundra ecotone could result in a shift from krummholz to symmetrical trees and/or from patch forest to continuous forest.
Keywords: Biology, Ecology.